Processos hidrogeoquímicos que controlam as características das águas dos reservatórios Poxim, Jacarecica II e Ribeira, situados no Estado de Sergipe - Silva, Rosahelena Reis Morais (2021)
In this study, the geochemical processes that control the chemical composition of the water stored in the Poxim, Jacarecica II and Ribeira reservoirs, located in the State of Sergipe, were investigated and identified. Surface water samples were collected in eight sampling campaigns carried out in the dry and rainy periods of the years 2013 to 2019. In each sample, data were determined the following parameters: pH, temperature, total dissolved solids (STD), HCO3 - , SO4 2- , Cl- , Na+ , K+ , Ca2+ e Mg2+ . The hydrogeochemical analysis was performed using the Gibbs diagram, Piper triangular diagram, ionic ratios and simulations with the inverse modeling using the PHREEQC computer program. The ionic abundance showed the order of concentration Ca2+> Na +> Mg2+> K+ for Poxim and Na+> Ca2+> Mg2+> K+ para os reservatórios Jacarecica II e Ribeira. Enquanto o domínio aniônico variou de HCO3 -> Cl-> SO4 2- for the Jacarecica II and Ribeira reservoirs. While the anionic domain exhibited the order of HCO3 -> Cl-> SO4 2- for the three reservoirs. The waters were classified by the Piper diagram, as bicarbonated for Poxim and chlorinated for Jacarecica II and Ribeira. The reservoir samples were distributed in the Gibbs diagram in the weathering region, indicating the water-rock interaction as the main process responsible for the chemical characteristics. The ionic ratios signaled as geochemical processes associated with the ionic composition of the waters, the dissolution of sea salt, calcite and silicate weathering for the Poxim reservoir, dissolution of sea salt, calcite, dolomite and silicate weathering for the Jacarecica II reservoir and dissolution from sea salt, calcite, dolomite, silicate weathering and ion exchange to the Ribeira reservoir. Inverse geochemical modeling was applied between two selected water samples, considering the variability observed in the dataset of samples collected for each reservoir. In the Poxim reservoir, the geochemical processes involved in the change in composition between the samples collected in January/2015 and June/2018 were the dissolution of halite associated with sea salt, calcite, direct ion exchange and biotite weathering. In the Jacarecica II reservoir, the dissolution of halite associated with sea salt, calcite, dolomite, the weathering of K-feldspar and biotite and the direct ion exchange process contributed to the variation of concentrations between the samples collected in January/2014 and January 2015. . While in the Ribeira reservoir, the geochemical processes involved in the alteration of the composition between the samples collected in August/2017 and June/2014 were the dissolution of halite associated with sea salt, dolomite, gypsum, biotite weathering and reverse ion exchange. In addition to the natural weathering process, the contribution of irrigation activity to the ionic composition of the waters of the Jacarecica II and Ribeira reservoirs was detected. For this reason, a more adequate management of irrigated agriculture areas is recommended, to reduce the speed of salinization of the reservoirs.